2008
DOI: 10.3813/aaa.918074
|View full text |Cite
|
Sign up to set email alerts
|

A Scale Model Study of Parallel Urban Canyons

Abstract: Shielded urban areas are of importance regarding urban citizens' annoyance and adverse health effects related to road traffic noise. This work extends the existing knowledge of sound propagation to such areas by a scale model study, rather than by model calculations. The scale model study was executed for two parallel urban canyons at a 1 to 40 scale, with a point source located in one canyon. Cases with acoustically hard façades and absorption and diffusion façade treatments were investigated. To correct for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Consequently, this concept has become part of the noise policy in a number of European cities [114]. Therefore, potentially quiet areas, like urban courtyards, have been studied in detail [115][116][117][118][119][120][121][122]. Although courtyards are often strongly shielded from direct exposure to road traffic noise, many of such places were found to exhibit noise levels that are too high to function as quiet areas [123].…”
Section: Building Envelope Greeningmentioning
confidence: 99%
“…Consequently, this concept has become part of the noise policy in a number of European cities [114]. Therefore, potentially quiet areas, like urban courtyards, have been studied in detail [115][116][117][118][119][120][121][122]. Although courtyards are often strongly shielded from direct exposure to road traffic noise, many of such places were found to exhibit noise levels that are too high to function as quiet areas [123].…”
Section: Building Envelope Greeningmentioning
confidence: 99%
“…This typical behavior in a non-directly exposed canyon was found as well based on the detailed scale modeling of adjacent city canyons described in Ref. 17. Time-domain simulations in Ref.…”
Section: Signal Processingmentioning
confidence: 95%
“…Like in room acoustics, in the aim to reduce noise level within street, the effective strategy based on correcting the acoustic properties of urban spaces can be used. Few studies suggested using absorption and diffusion devices as a façade treatment to reduce noise propagation, like absorbent patches on the façades, and on the ground [17] [18] or oriented ones on the façades [19].…”
Section: Forming Façade's Surface By Acoustic Diffusermentioning
confidence: 99%